N-METHYL-B-MESITYLDIBENZO-1,4-AZABORININE - THE 1ST EXPERIMENTAL STRUCTURE OF A 1,4-AZABORININE DERIVATIVE - Hampel, Frank; Clark, Timothy; et al. (Journal of the Chemical Society - Series Chemical Communications, 1992)
The structure of the 1,4-azaborinine ring in the title compound, a representative of a novel class of potentially aromatic compounds that are isoelectronic with arenes, confirms conclusions of earlier ab initio calculations that cyclic conjugation in 1,4-azaborinines is interrupted by the boron atom.